Transparency and Risk Allocation in PPP: Addressing Complex Contracts' Mathematical Formulas in the Portuguese Case (Lex localis - Journal of Local Self-Government, 2022)
Concept of partnership between public and private entities, commonly addressed as »Public private partnership« or PPP, have spread all over the world as an innovative model to deliver public services and to help established public infra-structure; as railways and roads, water supply facilities and sewerage systems, other communal services and public infrastructure, even building and managing hospitals, elderly homes, etc. In order to serve the public interest, PPP projects should be based upon a negotiated allocation of risk, which means that project risks should be distributed equaly between the partners. However, issues of transparency, good governance and public accountability have been at risk in the process. Through the Portuguese case of PPP involving the reward contract for the construction and maintenance of highways, the argument for the need of transparent and readable information is presented.